Tata Kelola Teknologi Informasi Dengan Metode Cobit 4.1 (Studi Kasus: Rumah Sakit IMC Bintaro) - Titin Kristiana (LPPM STMIK ANTAR BANGSA, 2017)
Abstract -Hospital Services in Indonesia in the present era is inseparable from the economic development which demands quality and quality. To support quality service and quality needed an information technology-based tools. IMC Bintaro Hospital started to use information technology in both the communication systems and information management systems the hospital, but the development is still found some problems in the application and processing of information systems for health care patients, not entirely related units using the modules available, the availability of hardware in service unit network system that has not been good and the management is not quickly and accurately obtain reports. The objective is to obtain information about the state of information technology governance and analyze the gaps. The framework used is COBIT 4.1 by using a domain DS and ME. Results of the study's findings is the level of maturity of the current state of information technology governance in the IMC Bintaro Hospital are at level 2 with a condition that is expected to reach level 3. Then analyzing the gaps and then made a recommendation strategies to address the gaps that exist so that the level of maturity that is expected to be achieved. Therefore, it can be concluded that there is still a gap between the current maturity level at level 2 with the expected maturity level at level 3Intisari - Pelayanan Rumah Sakit di Indonesia pada era sekarang tidak terlepas dari perkembangan ekonomi. Menyadari pentingnya pelayanan pasien terhadap pasien maka RS IMC Bintaro mulai menggunakan teknologi informasi baik dalam sistem komunikasi dan sistem informasiUntuk mendukung pelayanan yang berkualitas dan bermutu diperlukan suatu alat bantu berbasis teknologi informasi. RS IMC Bintaro mulai menggunakan teknologi informasi baik dalam sistem komunikasi dan sistem informasi manajemen rumah sakit, Namun dalam perkembangan masih ditemukan beberapa kendala dalam pengaplikasian dan pemrosesan sistem informasi terhadap pelayanan kesehatan pasien, belum seluruhnya unit terkait menggunakan modul yang tersedia, ketersediaan hardware di unit pelayanan, sistem jaringan yang belum baik dan manajemen belum secara cepat dan akurat mendapatkan laporan.Â Kata Kunci : Tata Kelola, Teknologi Informasi, Cobit 4.1